Deleuze and the animal - Gardner, Colin 1952- (Deleuze connections, 2017)
The first volume to address the animal in Deleuze's work, looking at philosophy, aesthetics and ethicsBecoming-animal is a key concept for Deleuze and Guattari; the ambiguous idea of the animal as human and nonhuman life infiltrates all of Deleuze's work. These 16 essays apply Deleuze's work to analysing television, film, music, art, drunkenness, mourning, virtual technology, protest, activism, animal rights and abolition. Each chapter questions the premise of the animal and critiques the centrality of the human. This collection creates new questions about what the age of the Anthropocene means by 'animal' and analyses and explores examples of the unclear boundaries between human and animal.